ЖАС ӨСПИРИМЛЕРДЕГИ ҲУҚЫҚБУЗАРЛЫҚТЫҢ АЛДЫН АЛЫЎДА ҲӘМ ОЛАРДЫ ҚАЙТА ТӘРБИЯЛАЎДА ПРОФИЛАКТИКАЛЫҚ ИЛӘЖЛАРДЫҢ ТУТҚАН ОРНЫ (Қарақалпақстан ишки ислер уйымларының 1946-1952-жыллардағы искерлиги мысалында) - Алламбергенов, Е.К. (SCIENCE and SOCIETY, 2017)
The article deals with the study of the law priority in prophylaxy of law violation. There has been analyzed the work of the bodies of internal affairs on the example of the experience of departments of internal affairs of the republic of Karakalpakstan in the 40-50-s of the last century.
Keywords: violation of law; prophylaxy of law violation; re-education; legal up-bringing; violation of law and crime; protection of social order; officers of the department of internal affairs; tecnogers without care; post and patrol officers; department of the work with children